The Influence of Bullying on The Mental Health of Class Xl Students at SMAN 15 Padang of the 2024/2025 Academic Year - Nadia Putri Erwanda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to find out how much bullying affects the mental health of grade XI students at SMAN 15 Padang for the 2024/2025 school year. The type of research used in this study is quantitative. The research population is 340 grade XI students registered in the 2024/2025 school year, with a sample of 22 students taken using non-random porposive sampling. The instrument used for data collection in this study is a questionnaire compiled according to the Likert model. Based on the results of a simple regression that the significance value is 0.001 < 0.005, it can be concluded that behavior has an influence on mental health. Data analysis using statistical programs on the SPSS 29 computer. Based on the data analysis carried out, the value of r is 0.808 while the r of the table is 0.422. Because the r calculation is greater than the r table (0.808 > 0.422), it means that there is a significant difference between bullying and the mental health of grade XI students of SMA Negeri 15 Padang. So it can be concluded that when bullying behavior can be overcome in the school environment, students' mental health tends to increase.